Efficient ozonation of reverse osmosis concentrates from petroleum refinery wastewater using composite metal oxide-loaded alumina - Yu Chen (KeAi Communications Co., Ltd., 2017)
Abstract Novel Mn–Fe–Mg- and Mn–Fe–Ce-loaded alumina (Mn–Fe–Mg/Al2O3 and Mn–Fe–Ce/Al2O3) were developed to catalytically ozonate reverse osmosis concentrates generated from petroleum refinery wastewaters (PRW-ROC). Highly dispersed 100–300-nm deposits of composite multivalent metal oxides of Mn (Mn2+, Mn3+, and Mn4+), Fe (Fe2+ and Fe3+) and Mg (Mg2+), or Ce (Ce4+) were achieved on Al2O3 supports. The developed Mn–Fe–Mg/Al2O3 and Mn–Fe–Ce/Al2O3 exhibited higher catalytic activity during the ozonation of PRW-ROC than Mn–Fe/Al2O3, Mn/Al2O3, Fe/Al2O3, and Al2O3. Chemical oxygen demand removal by Mn–Fe–Mg/Al2O3- or Mn–Fe–Ce/Al2O3-catalyzed ozonation increased by 23.9% and 23.2%, respectively, in comparison with single ozonation. Mn–Fe–Mg/Al2O3 and Mn–Fe–Ce/Al2O3 notably promoted ·OH generation and ·OH-mediated oxidation. This study demonstrated the potential use of composite metal oxide-loaded Al2O3 in advanced treatment of bio-recalcitrant wastewaters.